Morphology and mixing state of aged soot particles at a remote marine free troposphere site: Implications for optical properties. Issue 4 (18th February 2015) - China, Swarup; Scarnato, Barbara; Owen, Robert C.; Zhang, Bo; Ampadu, Marian T.; Kumar, Sumit; Dzepina, Katja; Dziobak, Michael P.; Fialho, Paulo; Perlinger, Judith A.; Hueber, Jacques; Helmig, Detlev; et al.
Abstract The radiative properties of soot particles depend on their morphology and mixing state, but their evolution during transport is still elusive. Here we report observations from an electron microscopy analysis of individual particles transported in the free troposphere over long distances to the remote Pico Mountain Observatory in the Azores in the North Atlantic. Approximately 70% of the soot particles were highly compact and of those 26% were thinly coated. Discrete dipole approximation simulations indicate that this compaction results in an increase in soot single scattering albedo by a factor of ≤2.17. The top of the atmosphere direct radiative forcing is typically smaller for highly compact than mass‐equivalent lacy soot. The forcing estimated using Mie theory is within 12% of the forcing estimated using the discrete dipole approximation for a high surface albedo, implying that Mie calculations may provide a reasonable approximation for compact soot above remote marine clouds.